Orientasi Kewirausahaan dan Pasar Serta Efeknya terhadap Kinerja Bisnis (Studi Kasus Pada Pelaku UMKM Olahan Pangan di Kabupaten Bone Bolango) - Ramlan Mustafa (AGRIMOR, 2023)
This research is expected to be able to determine the impact of entrepreneurial orientation and market orientation on business performance (Case Study on food processing MSME actors in Bone Bolango Regency) to a certain extent and at the same time. The data in this study were collected based on opinion polls or questionnaires. The number of respondents was 43 people.The research data was analyzed using multiple quantitative inferential regression.The results showed that (1) Enterprising direction significantly influences business implementation in food processing MSME actors in Bone Bolango Regency with a partial determination coefficient value of 22,30 %, (2) Market Orientation has an effect positive and significant impact on business implementation in food processing SMEs in Bone Bolango Regency with a partial determination coefficient of 35,10 % (3) Enterprising market and market orientation together have a positive and significant influence on business performance s in food processing SMEs in Bone Bolango Regency. The coefficient of determination is 57,40 % and the difference is 42,60 % which can be explained by other factors not analyzed in this review, such as management skills, business strategy, social capital, local wisdom and marketing mix effectiveness.